PENGARUH KECEMASAN IBU TERHADAP PROSES PERSALINAN KALA 1 FASE AKTIF DI BPS ATIK SUHARIJATI SURABAYA - Masruroh, Nur (Jurnal Ilmiah Kesehatan, 2015)
The relationship with the mother's level of anxiety in the first stage of labor active phase in BPM Atik Suharijati Surabaya. Mothers who experienced the process of labor is a physiological thing, but in reality people still think childbirth is a life and death stakes. Mothers who give birth experience anxiety levels cause birth becomes pathological. This study aims to determine the relationship with the mother's level of anxiety in the first stage of labor active phase in BPM Atik Suharijati Surabaya. Design analytical research with cross sectional approach. The population around the third trimester pregnant women who face labor in BPS Atik Suharijati in April-May 2015 of 25 respondents. A sample of 12 respondents in October was taken with the technique of "purposive sampling". Independent variables and the dependent variable levels of anxiety long active phase. Collecting data using questionnaires and partograf. Data were analyzed using the Mann Whitney test with a significance level a = 0.05. The results showed nearly half (41.7%) had mild anxiety and the majority of respondents (75%) had active phase <6 hours. Statistical test results obtained ? = 0.024 <? = 0.05, H0 is rejected means that there is a relationship with the mother's level of anxiety in the first stage of labor active phase in BPS Atik Suharijati. The conclusions of this study is the higher the mother's level of anxiety, the more disturbing the birth process to be gone through. So that health workers are expected to continue to provide information or understanding to pregnant women about childbirth and the factors that influence it.